Corrosion induced damage model for ductile fiber reinforced cementitious composites - Ahmed, Shaikh; Maalej, M.; Nikraz, Hamid (Computational Structural Engineering Institute of Korea, 2009)
This paper presents a finite element (FE) based numerical model to simulate the corrosion-induced cracking of reinforced beams containing ductile fiber-reinforced cementitious composites (DFRCC) and ordinary concrete. The strains obtained from the FE models are compared with that measured by the fiber-optic strain sensor (FOSS) gauge, which is placed between longitudinal steel bars at midspan of reinforced concrete (RC) beams during the accelerated corrosion test. The model could predict the corrosion-induced damage tolerance of DFRCC material and found that it is several times higher than that of ordinary concrete. The model predicted uniform damage in the DFRCC material due to corrosion compared with localized damage in ordinary concrete. The model also predicted that the delamination of the cover of the RC beams containing DFRCC material will occur at a higher level of steel loss compared with that of an ordinary concrete beam.